Sosialisasi Penggunaan Button Board Media Pembelajaran Berbasis Digital Bagi Peserta Didik Tunagrahita SLB Muhammadiyah Purworejo - Fadilla Nur Ramadhani; Tariska Widiastuti; Novita Iriyanti Ningrum; Umi Pratiwi (Faculty of Engineering UNHAS, 2022)
Learning media is an important element that acts as a tool in the teaching and learning process in the classroom which greatly affects students' interest in learning, especially in classes with mental retardation. However, there are still many uses of learning media that tend to be boring for students so that it affects the process of understanding the material. One solution to increase interest and motivation in learning for mentally retarded students to be more alive is by socializing the use of button boards as digital-based learning media for 10 class VI students with mental retardation at SLB Muhammadiyah Purworejo. This service is in the form of socialization which aims to provide new empirical knowledge and experiences for students with the nuances of digitalization technology. The implementation of this service is divided into 4 stages, namely the stages of analyzing, designing, designing, and implementing the use of the button board. Based on the results of the questionnaire that has been given, students experienced an increase in the curiosity aspect of the button board learning media by 30% and the aspect of students' understanding of the learning material increased by 10%. After the socialization, the students showed a response that the button board was very interesting and very helpful in understanding the material because their very great curiosity made their desire to try and learn higher. So it can be said that this service activity brings benefits and the use of the button board is considered effective and can be used as an alternative solution in classroom learning.